Patterned photocrosslinking to establish stiffness anisotropies in fibrous 3D hydrogels. (15th March 2022) - Jagiełło, Alicja; Hu, Qingda; Castillo, Ulysses; Botvinick, Elliot
Abstract: Cells are known to constantly interact with their local extracellular matrix (ECM) and respond to a variety of biochemical and mechanical cues received from the ECM. Nonetheless, comprehensive understanding of cell-ECM interactions has been elusive. Many studies rely on analysis of cell behavior on 2D substrates, which do not reflect a natural cell environment. Further, lack of dynamic control over local stiffness anisotropies and fiber alignment hinders progress in studies in naturally derived fibrous 3D cultures. Here, we present a cell-safe method of patterned photocrosslinking, which can aid in studying biological hypotheses related to mechanotransduction in 3D hydrogels. As previously described by our group, ruthenium-catalyzed photocrosslinking (RCP) of selected ECM regions promotes localized increase in stiffness mediated by focused blue laser light in a confocal microscope. In this study, we further demonstrate that RCP can induce localized strain stiffening and fiber alignment outside of the selected crosslinked region and induce stiffness anisotropy biased towards the direction of fiber alignment. MDA-MB-231 cells are shown to respond to RCP-induced changes in local ECM architecture and display directional bias towards the direction of fiber alignment, as compared to control cells. Further, the effect of patterned crosslinking on a stiffness landscape is measured using multi-axes optical tweezers active microrheology (AMR) with backscattered laser beam illumination. AMR validates RCP as a suitable tool for creating distinct stiffness anisotropies which promote directed migration of cells, further underscoring the usefulness of RCP in cell-ECM studies. Statement of significance: Studies on cell-ECM interactions in 3D cultures have often been hindered by the lack of available tools to dynamically alter local ECM stiffness and fiber alignment. Here, we present a non-invasive, cell-safe and easily applicable method of patterned photocrosslinking, which can aid in studying biological hypotheses in fibrous 3D hydrogels. Ruthenium-catalyzed crosslinking (RCP) of selected fibrin ECM regions promotes localized increase in stiffness and creates distinct stiffness anisotropies in the presence of the focused blue laser light. Outside of the crosslinked region, RCP causes fiber alignment and strain stiffening in the ECM, verified using multi-axes optical tweezers active microrheology (AMR). Following RCP, human breast cancer MDA-MB-231 exhibit directed cell migration, validating usefulness of this method in cell-ECM studies. Graphical abstract: Image, graphical abstract